METHOD TO POST-METHOD PEDAGOGY ADMINISTERED BY A CLASSROOM TEACHER IN THE TEACHING OF ENGLISH (A Case Study at a Senior High School in Bandung) - Dasep Suprijadi (Didaktik, 2014)
This study entitled “Method to Post-method Pedagogy Administered by a Classroom Teacher in the Teaching of English” intends to portray the teaching method and methodology used by the teacher in the teaching of English at the tenth grade of a senior high school in Bandung.  Looking at the purpose, it is obvious that the present study is descriptive in nature.  This study is guided by three research questions covering: 1) what is the expected method used by the teacher in the teaching process? 2) Do the procedures of the expected method conform to its theoretical principles? 3) What methodology is actually practiced by the teacher in the teaching process?  The data for this study were compiled through classroom visits. To attain comprehensive and accurate information about the teaching methods used by the classroom English teachers, this study utilized two techniques namely videotaping and document analysis. The study found out that: 1) the expected method, which is claimed to follow by the classroom English teacher is the Grammar Translation Method or GTM; nevertheless 2) The procedures of GTM conducted by the teacher are not exactly conforming to the principles of this expected method; 3) the methodology, which is actually practiced by the teacher in the classroom belongs to Language-centered method of which its principles characterize the actual procedures.  This study concludes that though the teacher claims that she uses the grammar translation method, as the method proposed by theorist, but the procedures that she actually conducted are in line with the various principles taken from several methods.